Patellar tendon properties and unilateral jump performance in junior elite volleyball players with patellar tendinopathy - Khair, R. M.; Finni, T.; Rantalainen, T.; Häyrinen, M.; Tapaninaho, K.; Köykkä, M. (European Journal of Sport Science, 2025)
Athletes with patellar tendinopathy (PT) seem to have superior jumping performance compared to asymptomatic counterparts. However, previous studies have primarily assessed bilateral tasks which does not capture unilateral impairments. Hence, this study aimed to assess the patellar tendon properties and unilateral jump performance, and their associations in volleyball athletes with and without PT. Lower extremity injury assessment, patellar tendon properties using shear wave (SW) elastography and comprehensive jump performance analysis were performed. From 27 athletes (16 females) included in the study, 13 had unilateral PT. Three-way ANOVA was used to evaluate the influence of PT. Differences between asymptomatic and symptomatic athletes were examined using simple contrasts. Moreover, we explored associations between patellar tendon properties and performance. Jump performance did not differ between or within asymptomatic and symptomatic athletes. In unilateral PT, the painful limb had lower SW velocity compared to the non-painful limb with a mean difference of -1.7 m × s-1 (95% CI -3.32 to -0.013 m × s-1) and compared to asymptomatic athletes -1.4 m × s-1 (95% CI -2.59 to 0.20). Regardless of condition, patellar tendon cross sectional area (CSA) was negatively correlated with jump height in both sexes. In males, CSA correlated negatively with SW velocity (r = -0.55, p = 0.008), while in females, SW velocity was negatively correlated with countermovement jump unweighting duration (r = -0.45, p = 0.023) and peak braking phase power (r = -0.60, p = 0.001). Jumping performance was not different in volleyball athletes with unilateral PT from their asymptomatic counterparts. Athletes with inferior jumping performance had larger patellar tendon CSA while tendinopathic tendons had worse patellar tendon properties.